The Ingenious Citizenship of The Paguyuban Ngesti Tunggal (PANGESTU) in Indonesia - Laela Fitriani Sahronie (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
This paper examines the practice of ingenious citizenship of an Indonesian spiritual group called Paguyuban Ngesti Tunggal (Pangestu), between their politics of religion (agama) and belief (kepercayaan). With the passing of the Constitutional Court Decision No. 97, 2017, the Indonesian government recognizes belief as another form of religious expression besides religion. Therefore, spiritual groups that are unable to be accommodated by religious or belief institutions have had difficulty accessing organizational rights, as they are considered ‘abject’ citizens. Even so, Pangestu has emerged as a spiritual group considered ‘abject citizens’ in the eyes of the state that has managed to survive. This paper will focus on two main questions: 1) How does the Indonesian government regulate citizens through the definition of religion and belief? 2) How does Pangestu respond to limited space for spiritual organizations between the recognition of religion and belief, by practicing ingenious citizenship? With these two formulations, this paper shows the relationship between the Indonesian government as an institution of control, and the spiritual organization of Pangestu as ingenious citizens. There will also be elaboration on strategies and unique tactics practiced by Pangestu to cope with the limited space given by the government.